Restriction maps of telomeres from Magnaporthe grisea - Mark L. Farman; Sally A. Leong (Fungal Genetics Reports, 1995)
At least five genetic maps exist for the rice blast fungus, Magnaporthe grisea (Romao and Hamer 1991 Proc. Natl. Acad. Sci. USA 89:5316-5320; Sweigard et al. 1993 in Genetic Maps, O'Brien ed. Cold Spring Harbor Press pp. 3.112-3.115; Skinner et al. 1993 Theor. Appl. Genet. 87:545-557; Hayashi and Naito 1993 in Abstracts for International Symposium on Rice Blast Disease, Madison, WI; and Tharreau et al. 1994 in Abstracts of 7th meeting of International Program on Rice Biotechnology, Bali, Indonesia). We have been integrating three of these maps by placing markers used in other laboratories on the map constructed in our laboratory (Skinner et al.. 1993, ibid.). The integrated map will be a primary reference map for this fungus and the Guy11 and 2539 parents used to generate the mapping progeny will become standard strains. Guy11 is a natural isolate; therefore this map provides information on the genome organization of a wild, rice-infecting isolate.